DIGITAL LITERACY AMONG TEACHERS IN SINGKAWANG CITY: AN ANALYSIS OF GENDER, AGE, AND SOCIO-ECONOMIC STATUS - Ariastya, Ribkah Melia; Karolina, Venny; Afandi, Afandi; Maria, Haratua Tiur (Journal of Educational Review and Research, 2023)
One of the demands of teachers in Generation Z is being able to have digital literacy content that supports their functions and work. There is no research related to the influence of gender, age, and socioeconomic status on digital literacy competency teachers in Singkawang City. This study aims to review whether there are significant differences in teachers' digital literacy abilities in terms of gender, socioeconomic status aspects of those who are able, moderate, or poor, and the age of teachers in different generations. This research method includes the descriptive quantitative inferential survey method. The number of volunteer respondents as research subjects was 200 teachers from 50 elementary and junior high schools who taught in Singkawang City and were selected by the voluntary response sampling technique. Data collection used a questionnaire instrument for teachers that contained 17 items that had been proven valid. Data were analyzed using the Mann-Whitney test for gender and the Kruskal-Wallish H test for age and socioeconomic status. The results showed that (1) the significance value was 0.063 > 0.005, which did not show a significant difference between teachers' digital literacy skills based on gender; (2) the significance value was 0.075 > 0.05, meaning that there was no difference in teachers' digital literacy seen from socioeconomic status (able, moderate, and underprivileged); and (3) the significance value is 0.106 > 0.05, indicating that there is no difference between teachers whose age includes the baby boomers generation, generation X, and the millennial generation